The New Shape of Global Higher Education in COVID-19 Era - Khalil, M.; Afifi, M. (SPC Journal of Education, 2020)
The effect of COVID-19 in the world made us face unprecedented challenges. It reflects a model of the Butterfly effect. The butterfly effect is the sensitive dependence on initial conditions in which a small change in one state of a deterministic nonlinear system can result in large differences in a later state. Governments have introduced emergency measures to save lives, Working from home has gone from perk to necessity, Lockdowns and closed borders have become part of 2020. As global citizens, it is crucial that we develop social responsibility towards each other to safeguard the entire humanity. At this stage, itâ€™s still impossible to say which phase of the pandemic we find ourselves in. Are we at the beginning of the end, or at the end of the beginning? Will we see a second wave of infections? When will a vaccine be ready? We are going through challenging times and the world around us is changing fast. We may not have all the answers to these ques-tions, but we do know that the world will witness lasting changes due to COVID-19 pandemic. COVID-19 as an international pandemic, has shed its profound impact on all daily aspects of life in the entire world; political, economic, social and apparently the education sector has not been immune.Â Â